Développement Testiculaire chez Poisson Combattant (Betta splendens), variété de Demi-lune, Subis 35 jours de Différents Régimes de Photopériodes - Rika Prihati Cahyaning Pertiwi; Isdy Sulistyo (MAIYAH, 2022)
Fighting fish (Betta splendens) is one of the fresh water ornamental fish with highly commercial value. This fish has a distinctive morphological shape which is aesthetic and is easy to maintain. Demand for this fish increased leading to opportunities for cultivation. Quality and quantity of fries were constantly needed, and this could be achieved by manipulating reproduction. Photoperiod regimes could play a role to do this. The purpose of this study was to determine the effect of photoperiods on the testis development of halfmoon strains of fighting fish. A completely randomized design was run to test 3 treatments in quintuplicates. The fish were reared under treatment P1 (10 hours light L and 14 hours dark D), treatment P2 (14 hours L and 10 hours D) and treatment P0 (12 hours L and 12 hours D). The fish were maintained for 35-d, in Aquatic Resources Laboratory of FPIK Unsoed. The results showed that treatment P2 was significantly different (P<0.05), which the highest spermatogenesis stage (54.78 ± 16.64%) was obtained. The study concluded that male fighting fish under P2 photoperiod could accelerate testicular maturation.